Determinants of Risk Factor of Preeclampsia Occurrence During Labor - Amalia, Rizki; Fathony, Zaiyidah; Riska, Riska; Hamidah, Hamidah (ProHealth Journal, 2024)
Preeclampsia complicates 2 to 4% of all pregnancies and causes approximately 46,000 maternal deaths and 500,000 fetal or newborn deaths each year. This study aims to determine the risk factors for preeclampsia, namely maternal age, parity, and hyperplacental disease (multiple pregnancies). The results of the relationship test between variables showed that p <0.05, which means that age, parity, and multiple pregnancies are related to the incidence of preeclampsia. Assessed from the confidence interval values ​​of the three variables studied, the age variable is a variable that can be generalized to the actual situation with a 95% CI value exceeding 1 (31.55 to 33.37). Health workers need to increase promotive and preventive efforts.